Optimizing Business Management with Electronic Customer Relationship Management Systems: A Case Study of Biotek Abadi - Ong, Pei Yee; Rosmamalmi Mat Nawi,; Ng Jie Kai, (Applied Information Technology And Computer Science, 2024)
Effective online Customer Relationship Management (eCRM) is indispensable for streamlined communication and collaboration. Biotek Abadi Sdn. Bhd., a scientific supplier in Malaysia, lacks a dedicated CRM system and currently relies on Microsoft Excel for sales and customer management. The Biotek Abadi Customer Relationship Management System (eBACRM) was introduced to minimize the time spent by users and provide an efficient platform for managing customer data. The implementation of the eBACRM system combines the prototyping model with the Analytic Hierarchy Process (AHP) modeling. This approach involves iterative refinements based on user feedback, ensuring the final product meets user needs effectively. Additionally, AHP modeling aids in prioritization and decision-making, enhancing the implementation process. Upon implementation, the eBACRM system aims to streamline the CRM process with a user-friendly interface.